Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fpsyg.2014.01486
|View full text |Cite|
|
Sign up to set email alerts
|

A question of scent: lavender aroma promotes interpersonal trust

Abstract: A previous study has shown that the degree of trust into others might be biased by inducing either a more “inclusive” or a more “exclusive” cognitive-control mode. Here, we investigated whether the degree of interpersonal trust can be biased by environmental factors, such as odors, that are likely to impact cognitive-control states. Arousing olfactory fragrances (e.g., peppermint) are supposed to induce a more exclusive, and calming olfactory fragrances (e.g., lavender) a more inclusive state. Participants per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Available evidence suggests that arousing fragrances, like peppermint, induce a more exclusive processing mode while calming scents, like lavender, induce a more integrative mode (e.g., Herz, 2009 ). Accordingly, Sellaro et al ( 2014b ) had participants play a Trust Game while being exposed to the scent of peppermint or lavender. As predicted, trustors transferred significantly more money to trustees in the lavender as compared to the peppermint and a control condition.…”
Section: Improving Trustmentioning
confidence: 99%
“…Available evidence suggests that arousing fragrances, like peppermint, induce a more exclusive processing mode while calming scents, like lavender, induce a more integrative mode (e.g., Herz, 2009 ). Accordingly, Sellaro et al ( 2014b ) had participants play a Trust Game while being exposed to the scent of peppermint or lavender. As predicted, trustors transferred significantly more money to trustees in the lavender as compared to the peppermint and a control condition.…”
Section: Improving Trustmentioning
confidence: 99%
“…In contrast to this, however, they observed that increasing serotonin availability actually increased the rejection of very unfair offers, which suggests that the effects of acute vs. prolonged boosting of serotonin may have opposite effects on social cognition. Sellaro et al (2015) also used a game setting to study the interaction between emotion and cognition. Participants in their study were exposed to social exclusion or ostracism, by observing someone else getting socially excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Once again, it turns out that our decisions are often not rationally taken at all and this study shows that the food we eat can alter the way we think about charity and foster helping behavior. In a third study, two of the authors of the previous study performed an experiment investigating the effect of an environmental factor (an arousing “peppermint” vs. a calming “lavender” olfactory fragrance) on social interactions while performing the Trust Game (Sellaro et al, 2015). In this game, participants can transfer money to an alleged trustee in order to index interpersonal trust.…”
Section: Introductionmentioning
confidence: 99%
“…Ambient scents have been shown to affect interpersonal trust, prosocial behaviors, and social communications [29,38]. For example, compared to a "no scent" condition, exposure to lavender scent can increase interpersonal trust, as measured by the amount of money one participant (the trustor) transfers to another participant (the trustee) during the "Trust Game" [38]. Body odors and fragrances worn by one another have also been found to modulate interpersonal behaviors and social communications [39][40][41].…”
Section: Introductionmentioning
confidence: 99%